Oncogenic KRAS, Mucin 4, and Activin A‐Mediated Fibroblast Activation Cooperate for PanIN Initiation - Hu, Chun‐Mei; Huang, Chien‐Chang; Hsu, Min‐Fen; Chien, Hung‐Jen; Wu, Pei‐Jung; Chen, Yi‐Ing; Jeng, Yung‐Ming; Tang, Shiue‐Cheng; Chung, Mei‐Hsin; Shen, Chia‐Ning; Chang, Ming‐Chu; Chang, Yu‐Ting; et al. (Advanced science, 2023)
Over 90% of patients with pancreatic ductal adenocarcinoma (PDAC) have oncogenic KRAS mutations. Nevertheless, mutated KRAS alone is insufficient to initiate pancreatic intraepithelial neoplasia (PanIN), the precursor of PDAC. The identities of the other factors/events required to drive PanIN formation remain elusive. Here, optic‐clear 3D histology is used to analyze entire pancreases of 2‐week‐old Pdx1‐Cre; LSL‐KrasG12D/+ (KC) mice to detect the earliest emergence of PanIN and observed that the occurrence is independent of physical location. Instead, it is found that the earliest PanINs overexpress Muc4 and associate with αSMA+ fibroblasts in both transgenic mice and human specimens. Mechanistically, KrasG12D/+ pancreatic cells upregulate Muc4 through genetic alterations to increase proliferation and fibroblast recruitments via Activin A secretion and consequently enhance cell transformation for PanIN formation. Inhibition of Activin A signaling using Follistatin (FST) diminishes early PanIN‐associated fibroblast recruitment, effectively curtailing PanIN initiation and growth in KC mice. These findings emphasize the vital role of interactions between oncogenic KrasG12D/+‐driven genetic alterations and induced microenvironmental changes in PanIN initiation, suggesting potential avenues for early PDAC diagnostic and management approaches. This study found that early PanIN cells express elevated levels of Muc4, specifically the oncogenic Muc4/X variant, and are closely associated with αSMA+ fibroblasts. This is observed in KrasG12D/+ transgenic mice and human pancreatic specimens with early PanINs. Importantly, upregulated Muc4 expression and Activin A secretion are identified as critical factors driving PanIN initiation in pancreatic cells with KrasG12D/+ mutation.